Assessment of clinical, functional and radiological outcomes in young patients with grade 3 and 4 osteoarthritis of the knee joint undergoing knee joint distraction with and without arthroscopic debridement and chondroplasty-a prospective, comparative and randomized controlled study - Gupta, Dinesh; Garg, Rohit N.; Adate, Amey Ashok (International Journal of Research in Orthopaedics, 2024)
Background: Treatment of severe osteoarthritis (OA) in relatively young patients is challenging. Although successful, Total knee arthroplasty (TKA) has a limited lifespan, with the risk of revision surgery, especially in active young patients. Our study aims to assess the comparative clinical, functional and radiological outcomes of knee joint distraction (KJD) with and without arthroscopic debridement and chondroplasty in OA of knee in the young, in a randomized controlled trial. Methods: Our study was a prospective randomized trial with equal allocation. A total of 160 patients needing intervention for knee arthritis, in the age group of <55 years were included as per the inclusion criteria, and were randomized into 2 groups. Group A included 80 patients who underwent KJD alone. Group B included 80 patients who underwent KJD with arthroscopic debridement and chondroplasty. All patients were followed up to 24 months post intervention. Clinical (Visual analogue scale-VAS), functional (Western Ontario and McMaster universities OA index-WOMAC) and radiological (Joint space width-JSW) outcomes were then compared and assessed. Results: Both the groups showed statistically significant improvement of clinical, functional and radiological outcome scores compared to baseline levels. The mean improvement in KJD+SCOPY group was statistically superior to that of KJD group with regard to clinical and functional outcome scores; however, the radiological improvement though being statistically significant in both groups compared to baseline levels, but one group was not superior to that of other. Conclusions: KJD in patients with OA of knee (Kellegren Lawrence grade 3-4) aged <55 years results in improvement of clinical, functional and radiological parameters at 2 year follow up. Addition of arthroscopic debridement and chondroplasty to KJD makes it superior to KJD alone in terms of improvement in clinical, functional and radiological outcomes. We recommend arthroscopic debridement and chondroplasty coupled with KJD for compliant patients of less than 55 years with grade 3-4 OA of the knee.